PET imaging of zirconium-89 labelled cetuximab: A phase I trial in patients with head and neck and lung cancer. Issue 2 (February 2017) - van Loon, Judith; Even, Aniek J.G.; Aerts, Hugo J.W.L.; Öllers, Michel; Hoebers, Frank; van Elmpt, Wouter; Dubois, Ludwig; Dingemans, Anne-Marie C.; Lalisang, Roy I.; Kempers, Pascal; Brans, Boudewijn; Winnepenninckx, Véronique; et al.
Abstract: Background and purpose: PET imaging of cetuximab uptake may help selecting cancer patients with the highest chance of benefit. The aim of this phase I trial was to determine the safety of the tracer 89 Zr-cetuximab and to assess tumour uptake. Methods: Two dose schedules were used; two consecutive doses of 60 MBq 89 Zr-cetuximab or a single dose of 120 MBq, both preceded by 400 mg/m 2 of unlabelled cetuximab. Toxicity (CTCAE 3.0) was scored twice weekly. PET-CT scans were acquired on days 4, 5 and 6 (step 1) or 5, 6, 7 (step 2). Because tumour uptake could not be assessed satisfactorily, a third step was added including EGFR overexpressing tumours. Results: Nine patients were included (6 NSCLC; 3 HNC). No additional toxicity was associated with administration of 89 Zr-cetuximab compared to standard cetuximab. A tumour to blood ratio (TBR) > 1 was observed in all but one patient, with a maximum of 4.56. TBR was not different between dose schedules. There was a trend for higher TBR at intervals > 5 days after injection. Conclusions: Both presented 89 Zr-cetuximab administration schedules are safe. The recommended dose for future trials is 60 MBq, with a minimum time interval for scanning of 6 days.